Body Weight as a Predisposing Factor for Humeral Condylar Fractures, Cranial Cruciate Rupture and Intervertebral Disc Disease in Cocker Spaniels - Brown, Dorothy Cimino; Conzemius, M. G.; Shofer, F. S. (Veterinary and Comparative Orthopaedics and Traumatology, 1996)
The purpose of this study was to determine whether or not body weight is a risk factor for humeral condylar fractures (HCF), cranial cruciate rupture (CCR) or intervertebral disc disease (IVDD) in the American Cocker Spaniel dog. Body weight, age, sex and recorded diagnoses of 854 Cocker Spaniels admitted to the teaching hospital, over a four-year period, were recorded from medical records. Dogs with a diagnosis of HCF (n = 21) weighed significantly more than the general population of Cocker Spaniels seen at the hospital over the same time period. Dogs with CCR (n = 20) were likely to weigh more than the general population. Whereas, dogs with IVDD (n = 47) weighed less than the general population of Cocker Spaniels. From these results, we concluded that body weight is a predisposing factor for HCF in Cocker Spaniels; that there is a tendency for Cocker Spaniels with CCR to be heavier than the general population and that being overweight does not predispose them to IVDD.Body weight, age, sex, and diagnoses of 854 Cocker Spaniels admitted over four years were recorded. Dogs with humeral condylar fractures weighed significantly more than the general population of Cocker Spaniels admitted over the same time period. Dogs with cruciate rupture weighed more, on average, than the general population of Cocker Spaniels, but surprisingly, dogs with intervertebral disc disease weighed less.
Keywords: Humeral condylar fracture; cranial cruciate rupture; intervertebral disc disease; body weight; dogs; Cocker Spaniel